Angiotensin II type 2 receptor (AT2R) as a novel modulator of inflammation in rheumatoid arthritis synovium. Issue 1 (December 2017) - Terenzi, Riccardo; Manetti, Mirko; Rosa, Irene; Romano, Eloisa; Galluccio, Felice; Guiducci, Serena; Ibba-Manneschi, Lidia; Matucci-Cerinic, Marco
Abstract Despite increasing evidence suggesting that angiotensin II type 2 receptor (AT2R) may regulate tissue inflammation, no study has yet analyzed its possible implication in rheumatoid arthritis (RA) synovitis. In this study, we investigated the expression and function of AT2R in synovial tissue and cultured fibroblast-like synoviocytes (FLS) from RA patients. AT2R expression was strongly increased in RA compared with osteoarthritis (OA) synovium, as well as in in cultured RA-FLS respect to OA-FLS and healthy FLS. Treatment with pro-inflammatory cytokines was able not only to boost AT2R expression in RA-FLS and OA-FLS, but also to induce itsde novo expression in healthy FLS. The stimulation of AT2R with the specific agonist CGP42112A significantly reduced gene expression of interleukin (IL)-1β and IL-6 and activation of NF-κB in RA-FLS, while opposite effects were elicited by AT2R small interfering RNA. Moreover, AT2R agonism efficiently decreased RA-FLS proliferation and migration either at baseline or under pro-inflammatory cytokine challenge. In conclusion, AT2R is strongly expressed in key effector cells of rheumatoid synovitis, namely RA-FLS, and the activation of AT2R with a specific agonist may effectively dampen their pro-inflammatory and aggressive behavior. AT2R agonism might represent a novel therapeutic strategy for patients with RA.